The International Finance Corporation and Forest Loss: A Cross-National Analysis - John Shandra; Eric Shircliff; Bruce London (Journal of World-Systems Research, 2015)
We conduct the first cross-national study to consider the impact of the World Banks International Finance Corporation loans on forests. In doing so, we analyze data for a sample of sixty-one low and middle income nations for the period of 1990 to 2005. We find substantial support for dependency theory that low and middle income nations that receive an International Finance Corporation loan tend to have higher rates of deforestation than low and middle income nations that do not receive such a loan. We also find that other aspects of World Bank lending affect forest loss including structural adjustment and investment lending. We conclude with a discussion of the findings, theoretical implications, methodological implications, policy implications, and possible directions for future research.